Analisa, Perancangan, dan Implementasi Sistem Menilai Kemajuan Kompetensi Peserta Pelatihan Secara Individu - Muhammad Fadhly Sani (Journal of Information System Research (JOSH), 2022)
The design of a system to assess the progress of the competence of individual trainees is one of the applications in the field of information and communication technology. This proves that information and communication technology affects the performance of the instructor in assessing the progress of the competency of the trainees held at the Banda Aceh Job Training Center. So far, the assessment of the progress of the trainees' competence is still done manually. So we need a computerized system so that it can make it easier to collect data on the progress of the competence of the trainees. To build this system, analysis, design, and implementation stages are carried out. The method used to carry out the system analysis and design process is using Data Flow Diagrams (DFD), Unified Modeling Language (UML), and system interface design. The system is built using PHP and MySQL database.Information Systems,